Patterns and Processes of Mycobacterium bovis Evolution Revealed by Phylogenomic Analyses - Patané, José S.L. (2017)
Mycobacterium bovis is an important animal pathogen worldwide, parasitizing wild and domesticated vertebrate live stocks as well as humans. We investigated evolutionary patterns and processes in 38 sequenced genomes of M. bovis from the Americas, Europe, Asia, and Africa. We found that US strains are evolving distinctly (though with low magnitude) from most South American lineages regarding core-coding size, GC-content, and codon usage bias, and we further employ agreement to this pattern as proxy for phylogenetic reliability. Three data types were used for tree inference: 1. Single copy core-coding genes (core-coding); 2. Indel blocks coded as numeric characters (indels); 3. Gene presence/absence similarly coded (pangenome). Core-coding´s performance was below expected regarded we used 2,000+ genes, but indels and pangenome individually estimated reasonable trees, with HGT rates as high as 200x the DNA substitution rate. In addressing why core-coding performed poorly, we excluded phylogenetic method bias, homologous recombination, positive, and purifying selection as possible causes, whilst transient retention of random mildly deleterious mutations due to recent diversification, and also ongoing pseudogeneization, may be plausible. Although total evidence´s retention index was as good as presence/absence data individually in identifying US samples, it additionaly found a South American clade with more lineages excluding only two Brazilian samples. We further inferred divergence times using indels + pangenome due to lack of informativeness of core-coding, recovering relatively similar date estimates to previous studies on the origin of M. bovis (< 10,000 y) regardless of the dating prior (strict vs. uncorrelated clock, uniform vs. exponential clock, different age/rate standard deviation priors), evincing the suitability and unsuspected robustness of using strictly genomic-wide presence/absence data to dating, while also decisively rejecting a strict clock for our dataset. All trees supported a relatively basal position of African strains, which were isolated from Homo sapiens, suggesting it was an important region for early diversification and confirming we were one of the earliest hosts of the species. Evolution of US strains was affected by lateral acquisition of 57 exclusive genes from, including genes important for virulence. A clade of three US localities, distant from one another, is under even faster evolutionary rates supported by core-coding, indels, and pangenome.